Relationship between organizational climate and management effectiveness - Arsenijević, Olja M; Jovanović, Larisa; Radosavljević, Milan Života (Industrija, 2017)
The subject of this research is the connection between management effectiveness in economic organizations of Vojvodina and creative organizational climate. According to that, scientific objective of our research is checking one of the most widely used model of measuring management effectiveness – Baldrige's model, on which is based system of management quality incentives in USA. Problem of this research can be expressed with following questions: Whether is possible that the company management in modern market conditions in AP Vojvodina, which has been designed as per traditional Taylor's model that started from the early stage of capitalism development, can be considered as effective? The key finding of this study can be expressed by the following conclusion: in a sample of observed organization the level of organizational creativity is at zero level. Ideas and behaviors inherent to creative organizational climate only born (average rating of level of creativity that all surveyed respondents gave was 0.396, and the median is 0.428). In an effort to concretize this finding, correlation analysis was undertaken between grouped variables of organizational creativity and potential factorial variables of organizational creativity.
Keywords: Creative organisational climate; Management; Creativity; Climate